Speed as an important component of football game - Milenkovic, D. (Acta Kinesiologica, 2011)
Speed as an important component of football games has an important place in the training process. The setting of today's football requires faster and faster players, that would be unpredictable and elusive for the opponent. For this reason, this investigation was concerned with speed in football in an attempt to understand the laws of its development. The study was conducted among 60 participants of football schools, 13 and 14 ± 6 months years of age in order to determine the relations between motor speed and the situational-motor speed in football. Motor speed as a predictor system consisted of eight tests: 1. Sprint speed: running speed at 20 meters, running speed at 50 meters, running speed at 60 meters, running speed at 100 meters and running speed at 200 meters. 2. Segmentary speed: foot taping, feet tapping on the wall and rotation of the foot. Criterion system of situational-motor speed in football were tested by: dribbling speed with obstacles, dribbling speed at a distance of 20m, dribbling speed with a change in direction at a 90º and dribbling speed by a semicircle. By using canonical correlation and regression analysis the obtained results have met expectations while working on this study and have showed a high level of relation of two observed areas, both at the multivariate level, and between some individual tests.